THE RELATIONSHIP BETWEEN INNER SPEECH IN ENGLISH AND SELF-CONFIDENCE AMONG LANGUAGE LEARNERS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This study explores how inner speech in English affects learners’ self-confidence. Students’ internal dialogue plays an important role in their comfort and ability to speak a new language. Using English in silent self-talk can help learners feel more confident and reduce anxiety, while a lack of inner practice may increase fear and hesitation. Encouraging learners to think in English and use inner speech regularly can create a positive psychological environment that supports better language learning and speaking performance.